Industrial training report: PRISM Integrated Sdn Bhd (Shah Alam) / Mohamad Rizal Ismail - Ismail, Mohamad Rizal (Perpustakaan Tengku Anis, 2015)
This paper has been write based on the trainee industrial training conducted for five months from August until December 2015 at PRiSM Integrated Sdn Bhd. The trainee has been placed under Operation, Marketing and Human Resource department. For the fourth month, the trainee involved Operation. The Human Resource Department for two weeks and Join Marketing & Sales for the next two weeks.The special project Digi Storing and Packing in PTPTN